Conceptual prevalence in palliative care amongst the physicians of Bangabandhu Sheikh Mujib Medical University: a comparison between the post-graduate trainees and the trainers (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background: Palliative care program has no place either in the national health care service or in undergraduate or post graduate medical curriculum in Bangladesh. Introduction: First Palliative Care Service began in the only medical university of the country in 2007 and still in its early infancy. We hypothesized that medical practitioners mostly have low level of understanding in palliative care Aim of the study: To assess the level of self- perception and understanding in palliative care amongst the post graduate trainees and their trainers in the university and to find out if there is any difference between the two groups. Materials and methods: 127 post graduate trainees and 81 post graduate teachers participated in a survey study during the first one year of the beginning of the service in the university. The data were collected after the survey and the responses were analyzed. Results: The reported level of perception in palliative care appeared to be present in both the groups even without any formal teaching or training. The trainees claimed to have more exposure and understanding than the post graduate teachers who happen to be their trainers. Actual level of understanding was difficult to assess. Conclusion: The result of this survey make a strong case of further evaluating the actual level of understanding and skill determination required in the field of palliative care in different institutions. This will enable to compare and to determine the sharp contrast for palliative care need versus lack of education and training in this field. DOI: http://dx.doi.org/10.3329/jbsa.v22i1.18098 Journal of BSA, 2009; 22(1): 26-31